Synthesis, Characterization and Study of Some N-Substituted Aryl-2- ({4-[(Substituted Aryl Carbamoyl) Methyl]-5-(Pyridin-4-yl)-4H-1, 2, 4-Triazol-3-yl} Sulfanyl) Acetamide: Synthesis, characterization and study of some 1, 2, 4-triazole. - Vikas Gopalrao Rajurkar,; Kiran Gadekar,; Vinayak K Deshmukh, (Iranian Journal of Pharmaceutical Sciences, 2014)
Pathogenic infections and inflammation are very common ailments humans suffer. Upsurge of resistant pathogens has impeded the antimicrobial drug development process in recent years and the search of new antimicrobial agents is clearly evident from the literature. In line with these developments the synthesis of N-substituted aryl-2-({4-[(substituted aryl carbamoyl) methyl]-5-(pyridin-4-yl)-4H-1, 2, 4-triazol-3-yl} sulfanyl) acetamide derivatives as antimicrobial, antioxidant and anti-inflammatory had been undertaken. The synthesis of target derivatives was achieved in three steps viz. potassium-pyridine-dithiocarbazate (II) obtained from base catalyzed reaction of isoniazide with CS2 which was further cyclized with hydrazine hydrate and CS2 to afford 4-amino-5-(pyridine-4-yl)-4H-1,2,4-triazole-3-thiol (III). This compound upon reaction with different aromatic N-substituted-α-chloroacetanilide afforded title compound N-substituted aryl-2-({4-[(substituted aryl carbamoyl) methyl]-5-(pyridin-4-yl)-4H-1, 2, 4-triazol-3-yl} sulfanyl) acetamides IV (KA1-KA15). All the newly synthesized derivatives were screened for in vitro antibacterial activity carried out against four bacterial strains viz. E.coli, K.pneumonia, S.aureus, and B. Subtilis and antifungal activity against two fungal strains viz. A.niger and S. cerevisiae by minimum inhibitory concentration (MIC) method, in vitro antioxidant activity was carried out by hydrogen peroxide radical scavenging method, and in vitro anti-inflammatory activity by inhibition of protein denaturation method. From the results of screening, it is evident that most of the derivatives KA3, KA4, KA7, KA9, KA11, and KA14 were found to possess promising biological activities and the derivatives with presence of electron-withdrawing groups at o-, m- and p- position of the phenyl ring improve the activity considerably.